Fatty acid composition and parasitism of European sardine (Sardina pilchardus) and anchovy (Engraulis encrasicolus) populations in the northern Catalan Sea in the context of changing environmental conditions. Issue 1 (29th December 2020) - Biton-Porsmoguer, Sebastian; Bou, Ricard; Lloret, Elsa; Alcaide, Manuel; Lloret, Josep
Abstract : The evaluation of fatty acids and parasitism at different reproductive and feeding stages of sardine and anchovy in the northern Catalan coast reveals the current poor condition of these populations linked to potential changes in planktonic productivity in the context of changing environmental conditions. Abstract: The status of sardine and anchovy populations in the northern Mediterranean Sea has been declining in recent decades. In this study, fatty acids and parasitism at different reproductive and feeding stages in these two species were assessed using specimens caught along the northern Catalan coast, in order to assess the links between lipid dynamics, reproduction and feeding in these two species and to contribute towards an explanation of the potential causes of the current poor situation of the stocks. The results support the use of fatty acid levels as indicators of the body condition of sardine and anchovy at different reproductive and feeding stages, as well as that of the pelagic environmental conditions. In particular, the relatively low n-3 polyunsaturated fatty acid levels found in spawning sardines compared to spawning anchovies indicate a poorer reproductive health status of sardine. By comparing the current total lipid content values with those recorded in other Mediterranean and North Atlantic areas, and others from more than 10 years ago, in the adjacent area of the Gulf of Lion, our study reveals the persistent poor condition of sardine and anchovy in the northern Catalan Sea. Furthermore, the low levels of diatom fatty acid markers observed throughout the spawning and non-spawning seasons in both sardine and anchovy indicate a diet poor in diatoms. Moreover, the results indicate that it is very unlikely that parasitism is a significant factor in the decline in condition of sardine and anchovy in the northern Catalan Sea. In fact, the results, which we believe provide useful insights for the management of small pelagic fisheries in the Mediterranean, suggest that the current poor condition of sardine and anchovy in the northern Catalan Sea has probably been exacerbated by a decrease in plankton productivity and/or a shift in the taxonomic composition of phytoplankton communities, adding to the ongoing effects of overfishing.